Revisiting Hill’s criteria: bridging historical foundations and modern epidemiological challenges - Ljubenović, Nenad; Nikolić, Vladimir (Medicinski časopis, 2025)
Causality is a cornerstone of epidemiological research, providing a framework for understanding the relationships between exposures and health outcomes. In his seminal 1965 paper, Sir Austin Bradford Hill proposed nine criteria to guide the evaluation of causal associations. These criteria - strength, consistency, specificity, temporality, biological gradient, plausibility, coherence, experiment, and analogy—continue to serve as foundational principles in modern epidemiology. However, the application of these criteria has evolved significantly in response to advances in scientific knowledge, statistical methodologies, and data availability. This paper revisits Hill’s criteria within the context of contemporary challenges and opportunities in public health research. It explores the nuanced interplay between causality and risk quantification, particularly in chronic and multifactorial diseases where direct causation is elusive. Through historical and modern examples, the paper illustrates the enduring relevance and adaptability of Hill’s framework. Additionally, the discussion emphasizes the importance of experimental and observational designs, the integration of advanced analytical techniques to emulate randomized trials, and the need to balance adherence to established principles with openness to novel discoveries. By revisiting Hill’s criteria, this work underscores their continuing utility in navigating the complexities of causality in a rapidly evolving scientific landscape.